Предмет: Алгебра,
автор: tankakvetik
одна вторая (-m-8n)в квадрате
MatemaU9:
упростить надр?
Ответы
Автор ответа:
1
Ответ:
1/4 * (m^2) + 4 * m * n + 16 * (n^2)
Объяснение:
( 1/2 * (-m - 8 * n) ) ^ 2 =
( 1/2 * (-m - 8 * n) ) * ( 1/2 * (-m - 8 * n) ) =
1/2 * 1/2 * (-m - 8*n) * (-m - 8 * n) =
1/4 * ( (-m) * (-m) + (-m) * (-8 * n) + (-8 * n) * (-m) + (-8 * n) * (-8 * n) ) =
1/4 * ( (m^2) + 8 * m * n + 8 * m * n + 64 * (n^2) ) =
1/4 * ( (m^2) + 16 * m * n + 64 * (n^2) ) =
1/4 * (m^2) + 1/4 * 16 * m * n + 1/4 * 64 * (n^2) =
1/4 * (m^2) + (16 / 4) * m * n + (64 / 4) * (n^2) =
1/4 * (m^2) + 4 * m * n + 16 * (n^2)
Автор ответа:
1
Объяснение:
Похожие вопросы
Предмет: Английский язык,
автор: artemrudenko0
Предмет: Русский язык,
автор: amir2v
Предмет: Русский язык,
автор: titanlab
Предмет: Математика,
автор: nastyagerc
Предмет: Русский язык,
автор: Sergey20055